PTU-131 Oesophageal Thermal Sensitivity and Mucosal Integrity in Healthy Subjects. A Study using a Novel Peltier-Based Heating Device and Impedance. (4th June 2013) - Al-Zinaty, M; Woodland, P; Reeves, J; Birch, M; Aziz, Q; Sifrim, D
Abstract : Introduction: Investigation of oesophageal sensitivity might help better improve phenotyping of patients with GERD, functional heartburn and non-obstructive dysphagia. Studies on oesophageal thermal sensitivity have used balloon techniques with circulating water. This lacks linear control of heating, has relative heat loss, and provokes mechanical stimulation by the distended balloon. Oesophageal mucosal integrity is important in symptoms perception and can be studied using impedance "in vivo". We developed a catheter device incorporating a "thermal stimulator" using Peltier heating technology and impedance electrodes to assess mucosal contact and integrity. We aimed to investigate oesophageal heat sensation/pain thresholds and their relationship with mucosal integrity in healthy human subjects. Methods: 21 healthy volunteers underwent thermal stimulation using an oesophageal catheter with a 7 mm electronic Peltier heater, to deliver a ramp heating protocol up to 60°C at 5 and 15 cm above LOS. Symptoms were recorded by computerised Visual Analogue Score (VAS). The delivered temperature at Pain Detection Threshold (PDT), time to PDT was measured and the area under the heating curve (AUC) was calculated. Oesophageal impedance was assessed over 10 minutes pre (basal), during and post heating in the distal and proximal oesophagus. The protocol was repeated after 2 weeks to assess reproducibility. Results: Temperature at PDT showed a very low SD in the distal and proximal oesophagus and Bland-Altman Tests showed good reproducibility (–0.1905 95% CI –1.4132 to 1.0327). There were no significant differences in thermal sensitivity parameters between distal and proximal oesophagus. Due to the low inter-individual variability in thermal sensitivity between healthy subjects, we could not find a significant correlation between impedance and perception parameters in the proximal or distal oesophagus. Conclusion: A novel Peltier-based thermal stimulator device can accurately and reproducibly determine oesophageal thermal sensitivity. In healthy subjects we could not demonstrate a correlation between basal impedance and sensitivity to heating. Current experiments are assessing this correlation in NERD patients with hypersensitivity to acid. Disclosure of Interest: None Declared